2021
DOI: 10.3389/fcvm.2021.701229
|View full text |Cite
|
Sign up to set email alerts
|

Hypercholesterolemia and Lymphatic Defects: The Chicken or the Egg?

Abstract: Lymphatic vessels are necessary for maintaining tissue fluid balance, trafficking of immune cells, and transport of dietary lipids. Growing evidence suggest that lymphatic functions are limited under hypercholesterolemic conditions, which is closely related to atherosclerotic development involving the coronary and other large arteries. Indeed, ablation of lymphatic systems by Chy-mutation as well as depletion of lymphangiogenic factors, including vascular endothelial growth factor-C and -D, in mice perturbs li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 82 publications
(104 reference statements)
0
3
0
Order By: Relevance
“…On the one hand, it may promote the expression of CD36, activates JAK1/STAT3, strengthens the lipid loading of macrophages, and accelerates the formation of foam cells; On the other hand, it can also reduce the inflammatory response by promoting the TGF-β and inhibiting IL-6, promotes the formation of plaque fibrous cap by increasing α-SMA, and enhances cholesterol efflux by up-regulating SR-B1. In addition, IL13RA1 also promotes the production of VEGF-C, which is believed to accelerate the process of plaque inflammation and lipid accumulation by promoting the formation of pathological lymphatics in the early stage of atherosclerosis [ 48 ], and also plays an active role in plaque regression and cardiac function recovery in the later stage [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, it may promote the expression of CD36, activates JAK1/STAT3, strengthens the lipid loading of macrophages, and accelerates the formation of foam cells; On the other hand, it can also reduce the inflammatory response by promoting the TGF-β and inhibiting IL-6, promotes the formation of plaque fibrous cap by increasing α-SMA, and enhances cholesterol efflux by up-regulating SR-B1. In addition, IL13RA1 also promotes the production of VEGF-C, which is believed to accelerate the process of plaque inflammation and lipid accumulation by promoting the formation of pathological lymphatics in the early stage of atherosclerosis [ 48 ], and also plays an active role in plaque regression and cardiac function recovery in the later stage [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lymphatic vessels exert a pivotal role in the regulation of fluid homeostasis, the conveyance of immune cells, and the transportation of lipids absorbed from dietary sources [60]. Recent studies have revealed that dysfunctional lymphatic vessels contribute significantly to the pathogenesis and progression of atherosclerosis within major arterial conduits.…”
Section: Conventional Calpain In Lymphatic Endothelial Cellsmentioning
confidence: 99%
“…The lymphocyte migration, originating from peripheral organs towards their respective lymph nodes, exhibited a discernible reduction concomitant with the onset of dyslipidemia [60]. Such lymphatic abnormality was subsequently ameliorated through the deficiency of conventional calpains, specifically within the lymphatic endothelial cells or myeloid cells [65].…”
Section: Conventional Calpain In Lymphatic Endothelial Cellsmentioning
confidence: 99%
“…Although the VEGF family is also involved in lymphangiogenesis, which may be related to VEGF-C and VEGF-D. 9 In chronic inflammatory conditions, such as in a mouse model of chronic colitis, VEGF-C enhances local lymphatic drainage and leads to the normalization of gut microbiota. 10 The high expression of VEGF-C and VEGF-D at the sites of inflammatory injury may be induced by macrophages 11 and mast cells 12 among others. VEGFR-3 is widely expressed in lymphatic endothelial cells (LECs) and can be activated by VEGF-C and VEGF-D, inducing LEC proliferation and migration.…”
Section: Introductionmentioning
confidence: 99%